Echocardiographic Evaluation of Atrial Septal Defects and Clinical Applications; A Focused Review (Bangladesh Heart Journal, 2022)
Atrial septal defect (ASD) is a commonly encountered congenital lesion in paediatric and adult populations and accounts for 8-10 % of all congenital heart disease. Echocardiography is the most sensitive and specific imaging tool to diagnose this condition and also to determine management guidelines. Various modalities of echocardiography imaging can assess atrial septal defects completely with associated changes in cardiac chambers, haemodynamic status, relationship with neighboring structures, suitability for percutaneous closure or need for surgical intervention. Echocardiography can guide percutaneous device closure procedure as well.Bangladesh Heart Journal 2022; 37(2): 130-138